TALABALARNING KASBIY KOMPETENTLIGINI RIVOJLANTIRIShDA FIZIKA VA TABIIY FANLAR INTEGRATSIYASIDAN FOYDALANISh METODIKASI - Begmatova, D.A.; Yakubova, B.A. (SCIENCE and SOCIETY, 2025)
This article presents the methodological foundations of teaching physics in integration with natural sciences such as biology, chemistry, and geography to develop students’ professional competence. The study scientifically substantiates the effectiveness of the integrative approach, systematic analysis in education, the use of practice-oriented tasks, and interactive teaching methods to ensure interdisciplinary connections. Furthermore, it highlights the opportunities for developing students’ critical thinking, problem-solving skills, and the effective application of scientific knowledge in professional contexts through the integration model.